THE INFLUENCE OF PERCEIVED ORGANIZATIONAL SUPPORT AND WORK ENGAGEMENT ON EMPLOYEE PERFORMANCE : (Study on Employees of PT Bank Tabungan Negara Medan Branch Office) - Josepin Siahaan; Ainun Mardhiyah; Onan Marakali Siregar (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
In today's dynamic and competitive business environment, organizations are increasingly recognizing the pivotal role that employee performance plays in achieving sustainable growth and maintaining a competitive edge. Consequently, understanding the factors that contribute to and influence employee performance has become a focal point for many contemporary organizations. Perceived organizational support and work engagement have emerged as two key variables that significantly impact employee performance and overall organizational effectiveness. This research aims to analyze the influence of perceived organizational support and work engagement on the performance of employees at the PT Bank Tabungan Negara (Persero) Medan Branch Office. This study employs quantitative research methods with a causal approach (cause and effect). The population comprises 158 employees from the PT Bank Tabungan Negara Medan Branch Office, with 61 employees participating as the sample. Data collection methods include questionnaires, observations, interviews, and data analysis using multiple linear regression analysis. The research findings reveal three significant conclusions: 1) Perceived organizational support significantly influences employee performance with a significance value of 0.046. 2) Work engagement significantly affects employee performance with a significance value of 0.000, indicating its strong impact. 3) Both perceived organizational support and work engagement jointly and significantly impact employee performance, with a significance value of 0.000, emphasizing their combined importance in enhancing employee performance at the organization.